ZNF24 regulates the progression of KRAS mutant lung adenocarcinoma by promoting SLC7A5 translation - Jia, Daqi; Li, Leilei; Wang, Peng; Feng, Qiang; Pan, Xinyan; Lin, Peng; Song, Shuling; Yang, Lilin; Yang, Julun (Frontiers in Oncology, 2022)
Background: Clinical treatment of RAS mutant cancers is challenging because of the complexity of the Ras signaling pathway. SLC7A5 is a newly discovered downstream gene of the Ras signaling pathway, but the regulatory mechanism is unclear. We aimed to explore the molecular mechanism and role in KRAS mutant lung adenocarcinoma progression. Methods: Key gene that regulated SLC7A5 in KRAS mutant lung adenocarcinoma was screened by RNA sequencing and bioinformatics analysis. The effect of this gene on the expression of SLC7A5 was studied by RNAi. The regulatory mechanism between the two genes was investigated by immunofluorescence, CoIP, pulldown and yeast two-hybrid assays. The location of the two genes was determined by inhibiting Ras and the downstream pathways PI3K-AKT and MEK-ERK. By in vivo and in vitro experiments, the effects of the key gene on the biological functions of KRAS mutant lung adenocarcinoma were explored. Results: We found a novel gene, ZNF24, which upregulated SLC7A5 protein expression rather than mRNA expression in KRAS mutant lung adenocarcinoma. Endogenous protein interactions occurred between ZNF24 and SLC7A5. Ras inhibition reduced the expression of ZNF24 and SLC7A5. ZNF24 and SLC7A5 are located downstream of the MEK-ERK and PI3K-AKT pathways. In vivo and in vitro functional experiments confirmed that the ZNF24-SLC7A5 signaling axis promoted the proliferation, invasion and migration of KRAS mutant lung adenocarcinoma. Conclusions: ZNF24 promoted the growth of KRAS mutant lung adenocarcinoma by upregulating SLC7A5 protein expression, which suggested that ZNF24 is a new biomarker of KRAS mutant tumors and could be a new potential therapeutic target for Ras-driven tumors.